Asuhan Kebidanan Komprehensif Pada NY “A” umur 27 Tahun dengan Riwayat Partus Prematurus Imminens pada Trimester II di Puskesmas Paguyangan Tahun 2024 - Meliyana; Himatul Khoeroh; Widi Astuti (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Imminent premature labor occurs at 20-37 weeks of gestation and the baby's birth weight is less than 2500 grams. Risk factors that cause imminent premature labor are bleeding, KPD, fetal growth retardation, fetal defects, twins, infection, preeclampsia and history of recurrent abortion. The purpose of the study was to provide comprehensive midwifery care with a history of imminent premature labor using midwifery management according to Varney and SOAP. The method used in this study was a qualitative descriptive method using a comprehensive case study approach. The results of the study were comprehensive midwifery care for Mrs. A found problems with a history of imminent premature labor, moderate anemia and KEK. Delivery was carried out normally pervaginally with labor induction. The newborn baby had mild asphyxia in the first minute and was normal in the 10th minute. The postpartum period was normal until the installation of the contraceptive, no complications or infections were found. The conclusion is that the comprehensive midwifery care that has been carried out on Mrs. A with a history of Imminent Premature Labor has complied with obstetric services and there have been no complications.